Breaking the ICE? Examining the Cognitive, Social, and Psychological Determinants of User Resistance to Electric Non-Road Work Vehicle Adoption - Jalo, Henri; Seppänen, Marko (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
The success of organizationally mandated technology adoption often hinges on whether employees are receptive or resistant to the new technology. This study examines non-road work vehicle operators’ attitudes toward switching to using electric work vehicles. A research model investigating the impact of cognitive evaluations of vehicle attributes, organizational social context, and psychological antecedents on resistance was tested using survey data from 1460 respondents collected via an online panel. Results from hierarchical multiple regression analysis show that beneficial vehicle attributes (perceived sustainability and quietness of electric work vehicles) and positive social context (colleague opinions and organizational adoption intentions) lower resistance. In contrast, psychological attitudes related to technostress and disrupting the status quo (techno-overload and inertia) significantly increase resistance. Theoretical contributions and practical implications of these findings are discussed.